(untitled) (Ibrahim Medical College Journal, 2009)
Various programs for safe motherhood aiming to reduce maternal and neonatal mortality are undertaken by public sectors as well as the NGOs. This descriptive cross-sectional study was conducted on the married women in their reproductive age (15-40y) belonging to 211 households of Shitlai village of Kahalu Thana of Bogra district in Bangladesh from January to April 2007. Using a semi-structured questionnaire, data were collected by door-to-door visits and through face-to-face interviews with the respondents. Considering the knowledge on safe motherhood and safe delivery, majority of the respondents (98.6%) mentioned that every pregnant mother should receive antenatal care, and 97.6% said that pregnancy is a period of risk. Regarding safety, 96.2% mentioned hospital delivery as safe, while 80.6% mentioned home delivery as a risk. Among the respondents, 70.1% said that ANC is important, 29.9% was found to be informed of child birth complications, 16.1% knew the duration of pregnancy, 8.1% knew the danger signs of pregnancy, 4.7% about emergency obstetric care (EOC), 4.3% about expected date of delivery (EDD), 2.4% about safe motherhood and 28.4% about the access of health facilities in the village. Among the respondents, 85.3% showed a positive attitude towards hospital delivery while 14.7% had a negative attitude. Study also showed that majority of the respondents (66.8%) had delivered at home, and only onefourth of the respondents delivered their index child in a hospital. Thus the study recommends to improve the knowledge, economic status, to change the decision making process through the launching of different activities with appropriate health programmes. Ibrahim Med. Coll. J. 2009; 3(1): 17-20 Key Words: Knowledge, attitude and practice (KAP), hospital delivery, married women doi: 10.3329/imcj.v3i1.2914